2002
DOI: 10.1016/s1010-7940(01)01121-6
|View full text |Cite
|
Sign up to set email alerts
|

Perivenous application of fibrin glue reduces early injury to the human saphenous vein graft wall in an ex vivo model

Abstract: Fibrin glue is able to accomplish adequate external vein graft support, preventing overdistention, in an ex vivo model. This provides a basis for clinical application. Further investigation is necessary to evaluate long-term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
0
17
0
6
Order By: Relevance
“…This includes pressure controlled preparation of the vein as well as harvesting of the vein with surrounding tissue and without distension (Hausmann et al, 1996;Souza et al, 2001Souza et al, , 2002. Furthermore, fibrin glue application may prevent overdistension after the saphenous vein graft has been inserted into the arterial circulation (Stooker et al, 2001(Stooker et al, , 2002(Stooker et al, , 2003.…”
Section: Implication Of the Present Study For Cabgmentioning
confidence: 99%
“…This includes pressure controlled preparation of the vein as well as harvesting of the vein with surrounding tissue and without distension (Hausmann et al, 1996;Souza et al, 2001Souza et al, , 2002. Furthermore, fibrin glue application may prevent overdistension after the saphenous vein graft has been inserted into the arterial circulation (Stooker et al, 2001(Stooker et al, , 2002(Stooker et al, , 2003.…”
Section: Implication Of the Present Study For Cabgmentioning
confidence: 99%
“…3 and 4) may lead to different fibrin glue concentrations within the vessel wall compartments and may exert different effects. Previous in vitro experiments have revealed that early distension could be diminished by external fibrin glue support [7,9,11] and in vivo experiments have furthermore revealed that perivenous support of vein grafts with fibrin glue can attenuate the severe injury encountered in the non-supported vein grafts exposed to arterial pressure at early time points after grafting [10]. However, at later time points it was demonstrated that external fibrin support showed negative or even detrimental effects on vein grafts [12].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce wall shear stress and to prevent the proposed negative effects of early vein graft distension due to arterial pressure, several 'extra vascular support' strategies have been introduced. These include the placement of a porous, non-restrictive, polyester stent [5][6][7], or a bio absorbable sheath [8] or the use of perivenous application of fibrin glue [9]. Perivenous fibrin glue has been used in a variety of experimental models and for different follow-up times [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To simulate the effects of grafting into the coronary circulation, 10 cadaveric RAs with minor ostial intimal tears were perfused ex vivo after harvest with Hank's solution for 30 minutes using a pulsatile perfusion pump (Masterflex L/S, Cole-Parmer Instrument Co, Vernon Hills, IL), as described [16]. Flow into the RA was initiated at 50 mL/min and titrated to maintain pressure of 80 to 110 mm Hg, as monitored by a pressure transducer catheter (Mikro-Tip, Millar Instruments, Inc, Houston, TX).…”
Section: Ex Vivo Radial Artery Perfusion Analysismentioning
confidence: 99%